Jack A. Holloway III letter to Thomas Kent about rare bird sighting of Tundra Swan at Snyder Bend in 1982 - Holloway III, Jack A.et al (1982)
Letter about a Tundra Swan sighting at Snyder Bend near Sioux City in Woodbury County, IA on March 13, 1982. It is from Jack Holloway III to Thomas Kent and contains details about other bird sightings. Epson - sheet feed/flatbed